Learning legal ethics in the law clinics: ‘one hundred thousand housing law’ for offences against minors (2019)
In the process of teaching law, is necessary to address some aspects that are not framed in strictly legal knowledge and require different strategies to be approach by the professor. An example of this, are the cases that a legal clinic knows, where a series of ethical dilemmas are posed to the student and it is important to provide it with the necessary tools to understand the problem from the values, have the ability to deliberate and make decisions that are fair and appropriate to the reality of the context and the particularities of the case. This paper aims to reflect on the ethical dilemmas that arise when weighting ethical and legal principles, through a case that raises the need to analyse the constitutionality of a rule and its existence within the legal system of the State. Likewise, through the real cases, as this one, students are in contact with a reality that seems far away and understand the importance of their knowledge and values in order to resolve the problematic that vulnerable groups. © 2019, © 2019 Informa UK Limited, trading as Taylor and Francis Group.